The Effect of Honey, White and Brown Table Sugar on Lipid Profile and Glucose Level in Rats - Tuffour, D.K. (University of Ghana, 2020)
Background: Honey and table sugar are commonly used sweeteners by many consumers. These sweeteners are examples of disaccharide sugar which forms part of the complex macromolecule, carbohydrate. Excessive consumption of dietary sugars including table sugar and honey is associated with several metabolic abnormalities and adverse health conditions such as obesity, diabetes and cardiovascular disease. There is a general debate by many researchers and consumers that honey is better than brown sugar which is also better than white sugar. However, scientific data supporting these claims are inconclusive on the effect of these natural sweeteners on the various biomarkers of cardio vascular health and glycaemia. Aim: The aim of the study was to determine the effect of honey, white and brown table sugar on lipid profile, glucose level and pancreatic insulin level and histology using animal models. Methodology: Thirty-five (35) male Sprague Dawley rats aged 12 - 14 weeks, weighing 150g - 250g were obtained. The groups were set up as follows: Group 1 (G1) – control group, group 2 (G2) - white sugar low dose 0.055 g (WS LD), group 3 (G3) - white sugar high dose 0.22 g (WS HD), group 4 (G4) - brown sugar low dose 0.057 (BS LD), group 5 (G5) - brown sugar high dose 0.230 g (BS HD), group 6 (G6) - honey low dose 0.076 g (H LD) and group 7 (G7) - honey high dose 0.304 g (H HD). One (1) ml of the prepared white sugar, brown sugar or honey solution was administered daily to the treatment group of rats orally by gavage for 12 weeks. After a 12 week administration period, the rats were sacrificed for blood and tissue analysis. Four millimetres (4ml) of blood samples was collected for analysis of lipid profile (total cholesterol, total triglycerides, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol) glycated haemoglobin (HbA1c) and fasting blood glucose (FBG). The harvested organ was weighed and divided into two parts. Half went into buffered formalin and the other half went into a container and stored at -80°C for insulin analysis. The pancreas was homogenized using dounce tissue grinder in cold PBS, for each 1 g of pancreas. The sample was centrifuged at approximately 10000 X g for 5 min. The supernatant was collected and insulin was measured. Two way ANOVA was used to compare the means within and between the treatment groups. Where ANOVA was significant, the post hoc test was performed using Bonferroni analysis. A p-value ≤ 0.05 was deemed statistically significant. Results: In this study, the assessed body weights of animals showed clear and continuous weight gain throughout the treatment groups, even though the difference was not significant between the groups. Also, the effect of intake of the three natural sweeteners white sugar, brown sugar and honey on the HbA1c, glucose level and lipid profile of the rats showed a significant increase in the high dose groups compared to the control group. Furthermore the effect of white sugar brown sugar and honey on the insulin levels of rats showed a significant decrease in insulin level of the high dose groups compare to the control group. However, the effect of white sugar, brown sugar and honey on insulin showed no significant difference between low dose groups when compared with the control group. Conclusion A twelve week treatment of honey, white and brown table sugar was found to cause an appreciable increase in FBG, HbA1c and lipid profile and release of insulin at the same dose. The increase was found to occur mostly in the high doses than in low doses with a few disparity.
MSc. Dietetics
Keywords: Table Sugar; Dietary sugars; Natural sweeteners; Obesity; Diabetes; Cardiovascular diseases